Transcriptional Regulation of Cysteine and Methionine Metabolism in Lactobacillus paracasei FAM18149 - Wüthrich, Daniel; Wenzel, Claudia; Bavan, Tharmatha; Bruggmann, Rémy; Berthoud, Hélène; Irmler, Stefan (Frontiers in Microbiology, 2018)
Lactobacillus paracasei is common in the non-starter lactic acid bacteria community of raw milk cheeses. This species can significantly contribute to flavor formation through amino acid metabolism. In this study, the DNA and RNA of L. paracasei FAM18149 were sequenced using next-generation sequencing technologies to reconstruct the metabolism of the sulfur-containing amino acids cysteine and methionine. Twenty-three genes were found to be involved in cysteine biosynthesis, the conversion of cysteine to methionine and vice versa, the S-adenosylmethionine recycling pathway, and the transport of sulfur-containing amino acids. Additionally, six methionine-specific T-boxes and one cysteine-specific T-box were found. Five of these were located upstream of genes encoding transporter functions. RNA-seq analysis and reverse-transcription quantitative polymerase reaction assays showed that expression of genes located downstream of these T-boxes was affected by the absence of either cysteine or methionine. Remarkably, the cysK2-ctl1-cysE2 operon, which is associated with te methionine-to-cysteine conversion and is upregulated in the absence of cysteine, showed high read coverage in the 5'-untranslated region and an antisense-RNA in the 3'-untranslated region. This indicates that this operon is regulated by the combination of cis- and antisense-mediated regulation mechanisms. The results of this study may help in the selection of L. paracasei strains to control sulfuric flavor formation in cheese.